FENOMENA EARNINGS MANAGEMENT SEBAGAI SEBUAH KECURANGAN - Lestari, Yona Octiani (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2010)
This paper describes management earnings that is the way using by manager to influence systematic profit number and intend by chosening policy of accounting and accountancy procedure. Phenomenon of Earnings management like two sides currency. On one side (good), management earnings is ' legitimate' product, while on the other side (bad), earnings management is considered to be product from an ' immoral' and ' unethical’ action There is three motivations in earnings management, that is capital market motivation that is accounting information by financial analysis and investor assisting price of stocks, contract motivation relates to long-term debt, that is manager boosting up net profit to lessen possibility of natural company of default technical (Healy : 1985) and motivation of regulation happened because government obliges financial statement in the form of accountancy number finally also generates the problem of earnings management conducted by managemen, because from manager exploits weakness of accountancy using estimation of accrual and election of accountancy method. Earnings management represent an action of immoral. Although earnings management is made to Standard Accountancy, but it is meaningless of earnings management represent smart action to legitamate of fraud.Keyword: Earnings Management, Manager Motivations , Ethical Behaviour